The Effect of Oil Price, Inflation, and Net Exports on Economic Growth in Indonesia the Period of 1980-2015 - Lasma Hutagalung (ProBisnis : Jurnal Manajemen, 2022)
The Gross Domestic Product (GDP) is one of the indicators of the success of the economic growth. As a developing country, Indonesia has a moderately good economic growth because it increases from year to year. This study to find out the effect of world oil price, inflation, and net exports to economic growth in Indonesia. This study employed the quantitative approach. The data were secondary data in 1980-2015. The data analysis technique in the study was the time series data analysis using the OLS (Ordinary Least Square). The results of this study indicate that the variable oil prices and net exports have a positive and significant impact on economic growth in Indonesia. This can be interpreted if the oil price and net exports increase, the economic growth in Indonesia will also increase. While the inflation and dummy variables have a negative and insignificant effect on economic growth in Indonesia. This can be interpreted, if inflation and dummy increase, then economic growth in Indonesia will decrease